Annual climate variation modifies nitrogen induced carbon accumulation of Pinus sylvestris forests. Issue 6 (10th July 2017) - Lim, Hyungwoo; Oren, Ram; Linder, Sune; From, Fredrik; Nordin, Annika; Fahlvik, Nils; Lundmark, Tomas; Näsholm, Torgny
Abstract: We report results from long‐term simulated external nitrogen (N) input experiments in three northern Pinus sylvestris forests, two of moderately high and one of moderately low productivity, assessing effects on annual net primary production (NPP) of woody mass and its interannual variation in response to variability in weather conditions. A sigmoidal response of wood NPP to external N inputs was observed in the both higher and lower productivity stands, reaching a maximum of ~65% enhancement regardless of the native site productivity, saturating at an external N input of 4–5 g N·m −2 ·yr −1 . The rate of increase in wood NPP and the N response efficiency (REN, increase in wood NPP per external N input) were maximized at an external N input of ~3 g N·m −2 ·yr −1, regardless of site productivity. The maximum REN was greater in the higher productivity than the lower productivity stand (~20 vs. ~14 g C/g N). The N‐induced enhancement of wood NPP and its REN were, however, markedly contingent on climatic variables. In both of the higher and lower productivity stands, wood NPP increased with growing season precipitation ( P ), but only up to ~400 mm. The sensitivity of the response to P increased with increasing external N inputs. Increasing growing season temperature ( T ) somewhat increased the N‐induced drought effect, whereas decreasing T reduced the drought effect. These responses of wood NPP infused a large temporal variation to REN, making the use of a fixed value unadvisable. Based on these results, we suggest that regional climate conditions and future climate scenarios should be considered when modeling carbon sequestration in response to N deposition in boreal P. sylvestris, and possibly other forests.